Signaling Strategies for Innovative Design: A Study on Design Tradition and Expert Attention - Micheli, Pietro; Gemser, Gerda (The Journal of product innovation management, 2016)
There is increasing acknowledgement that innovative product design has a positive effect on financial performance. However, innovative design may require specific efforts to aid interpretation and appreciation by the market. So far, little is known about how companies can enhance their chances of success when introducing innovative designs. This study contributes to the development of this area of research. Drawing on signaling theory, it examines the role of two types of signals that may act as enablers for market acceptance of innovative design: adherence to a national design tradition, and attention from experts and specialized media. Using data collected from Danish design‐intensive companies, findings show that design innovativeness has a positive impact on financial performance. The analyses demonstrate that the effect is reinforced if a novel design adheres to a national design tradition. In addition, novel designs will be more positively accepted if they receive attention from design experts and attract media coverage. Research also contributes to signaling theory, as it shows how intrinsic—design innovativeness and adherence to a design tradition—and extrinsic—expert and media attention—cues interact and influence financial performance. The paper concludes by discussing managerial implications, particularly in relation to the new product development process and the role of design, and by suggesting avenues for further research.